Disaster risk management and social responsibility in the Regional Government of Tacna, 2019 - Cabrera Huayhua, Juan Erik (2021)
The objective of this research was to determine the relationship between disaster risk management and social responsibility in the Regional Government of Tacna, 2019, a quantitative approach, basic type, correlational level, non-experimental design and cross section was used. The sample consisted of 174 workers, selected by random sampling who answered two instruments that measure disaster risk management and social responsibility, both with validity and reliability. It was reported that 64.9% of the staff considered the disaster risk management characteristic of this institution to be of a regular level, the most prominent dimension being corrective management; Likewise, 67.2% considered social responsibility as a regular level, the type of external dimension being the most prominent. Likewise, a significant and direct correlation was reported between both variables (p-value = 0.000; Rho = 0.793). It is concluded that there is a direct and high significant relationship between disaster risk management and social responsibility in the Regional Government of Tacna.